Community participation in formulating the post-2015 health and development goal agenda: reflections of a multi-country research collaboration - E Brolan, Claire; Hussain, Sameera; A Friedman, Eric; Lorena Ruano, Ana; Mulumba, Moses; Rusike, Itai; Beiersmann, Claudia; Stewart Hill, Peter (© 2014 BioMed Central Ltd., 2017)
This article was published in International Journal for Equity in Health [© 2014 BioMed Central Ltd.] and the definite version is available at: https://equityhealthj.biomedcentral.com/articles/10.1186/s12939-014-0066-6